Educational Impact and Trends of Ethnic Language Loss in Bangladesh: A Statistical and Policy-Based Review (2013-2023) - Ritesh Karmaker (Bumi Publikasi Nusantara, 2025)
This paper investigates the declining use of ethnic minority languages in Bangladesh over the last decade (2013–2023), with particular attention to the role of education in accelerating or mitigating this trend. Using a statistical approach supported by field data, the study examines language shift patterns across various regions, educational levels, and policy changes. Findings reveal a steady decline in the use of indigenous languages, exacerbated by national curricula that prioritize Bengali and English, as well as the lack of multilingual teacher training. Educational policies often neglect the linguistic rights of minority communities, leading to reduced intergenerational language transmission. The paper argues that integrating indigenous languages into school systems, providing culturally responsive materials, and training bilingual educators could reverse the trend. The study contributes both quantitative evidence and policy recommendations for revitalizing endangered languages in education and beyond.